A five year retrospective study of paediatric tuberculosis patients registered in Nanded Municipal Corporation - Potdar, Pralhad Sureshrao (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis (TB) is one of the most serious infections in the world contributing one third of the world’s population. Near about 11% of the childhood mortality and morbidity caused by tuberculosis worldwide, especially in developing countries. The aims and objectives of this study were to study retrospectively the clinical profile and treatment outcome of paediatric TB cases treated under RNTCP. Methods: An observational record based study was conducted among paediatric patients registered under Revised National Tuberculosis Control Programme (RNTCP) in NANDED city to know their disease profile from 2011- 2015. Results: In this study, the mean age of the study subjects was 10.58 years, most of them were in the 11-14 year age group (62.9%) followed by 6-10 years (25%) and 0-5 years (12.1%) respectively. with a female to male ratio of 6.1: 3.8. There were more cases of tuberculosis among female children with significantly more girls (61.4%) than boys (38.6%) {χ2=8.924, p< 0.01154 (S)} and 46.2% of them had extra pulmonary TB. Out of total (132), pulmonary TB cases were (53.8%) and among the extra pulmonary TB cases, tuberculous lymphadenitis (26.5%) was the commonest form for all ages followed by Abdominal Koch’s in 9.1%. Category I and II was started on 91.7% and 8.3% patients respectively. Overall, treatment completion rate was 82.5% and the default rate was 2.3% with a cure rate of 15.2%. More than one fourth of the study subjects gave a history of contact with tuberculosis patient. Conclusions: The probable reason for more prevalence of TB among females may be due to, neglected female child’s nutrition and health status in society. Paediatric tuberculosis still continues to be a major problem in 1-5 years of age who are undernourished and belonging to lower socioeconomic status.